3D Porous Hydrogel/Conducting Polymer Heterogeneous Membranes with Electro‐/pH‐Modulated Ionic Rectification. Issue 44 (12th October 2017) - Bao, Bin; Hao, Junran; Bian, Xiujie; Zhu, Xuanbo; Xiao, Kai; Liao, Jingwen; Zhou, Jiajia; Zhou, Yahong; Jiang, Lei
Abstract: Heterogeneous membranes composed of asymmetric structures or compositions have enormous potential in sensors, molecular sieves, and energy devices due to their unique ion transport properties such as ionic current rectification and ion selectivity. So far, heterogeneous membranes with 1D nanopores have been extensively studied. However, asymmetric structures with 3D micro‐/nanoscale pore networks have never been investigated. Here, a simple and versatile approach to low‐costly fabricate hydrogel/conducting polymer asymmetric heterogeneous membranes with electro‐/pH‐responsive 3D micro‐/nanoscale ion channels is introduced. Due to the asymmetric heterojunctions between positively charged nanoporous polypyrrole (PPy) and negatively charged microscale porous hydrogel poly (acrylamide‐ co ‐acrylic acid) (P(AAm‐ co ‐AA)), the membrane can rectify ion transmembrane transport in response to both electro‐ and pH‐stimuli. Numerical simulations based on coupled Poisson and Nernst–Plank equations are carried out to explain the ionic rectification mechanisms for the membranes. The membranes are not dependent on elaborately fabricated 1D ion channel substrates and hence can be facilely prepared in a low‐cost and large‐area way. The hybridization of hydrogel and conducting polymer offers a novel strategy for constructing low‐cost, large‐area and multifunctional membranes, expanding the tunable ionic rectification properties into macroscopic membranes with micro‐/nanoscale pores, which would stimulate practical applications of the membranes. Abstract : 3D porous hydrogel/conducting polymer heterogeneous membranes with electro‐/pH‐modulated ionic rectification are fabricated by electrochemically depositing nanoporous conducting polymer polypyrrole onto a hydrogel polyacrylamide–poly(acrylic acid) substrate. The facilely prepared heterogenous membranes with 3D interconnected channels may find numerous applications in sensors, biomolecular sieves, and energy‐conversion devices.